2020
DOI: 10.1371/journal.pone.0227360
|View full text |Cite
|
Sign up to set email alerts
|

Short- & long-term effects of monetary and non-monetary incentives to cooperate in public good games: An experiment

Abstract: Using a common experimental framework, this paper addresses both the question of the short-term and the long-lasting effects of temporary monetary and non-monetary incentive mechanisms on increasing individual contributions to the public good. The results show that both punishments and rewards significantly increase contributions compared to the baseline, but that monetary sanctions lead to the highest contributions, whereas non-monetary sanctions lead to the lowest contributions. The four types of incentives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
1
10
0
3
Order By: Relevance
“…However, it is worth noting that although social incentives increased cooperation compared to instances when incentives were absent, the increase in cooperation was higher in the presence of centralized financial incentives than in the presence of social incentives. This finding corroborates previous work comparing the effect of peer-delivered financial and social incentives on cooperation [ 16 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, it is worth noting that although social incentives increased cooperation compared to instances when incentives were absent, the increase in cooperation was higher in the presence of centralized financial incentives than in the presence of social incentives. This finding corroborates previous work comparing the effect of peer-delivered financial and social incentives on cooperation [ 16 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, although studies employing a peer system of incentive delivery have shown that both financial and non-monetary sanctions and rewards can increase cooperation rates [ 16 , 17 , 18 , 19 ], most experiments studying the effect of centralized incentives on cooperation have focused solely on financial rewards and punishments in an effort to shape behavior. However, society also implements, and indeed increasingly uses, social incentives, which typically operate via more affective mechanisms rather than the reward trade-offs encouraged by financial incentives.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the two incentive types there is evidence that financial incentives have proven to be more durable than non-price information strategies without equivalent (Ito et al 2018;Masclet et al 2003; see also Dolan and Metcalfe 2015;Lefebvre and Stenger 2020). Thus, it is conceivable that customers will have a higher motivation to reach the thresholds of the vouchers as compared to the certificates treatment at the end of the pilot phase.…”
Section: Related Literature and Research Hypothesismentioning
confidence: 99%
“…For example, the Pigovian tax or cap-and-trade emission requires relatively high administrative and monitoring costs to be successfully implemented. Secondly, the effect of monetary policies is not always sustainable in the long run [ 5 , 6 ]. Several studies have shown that environmental conservation programs cannot be easily achieved if they fail to motivate people in terms of environmental sustainability: Will people continue to conserve energy if they know that they will not receive any more payments for their efforts in the future [ 7 , 8 ]?…”
Section: Introductionmentioning
confidence: 99%